State-of-the-Art Pediatric Coronary Artery Bypass Surgery: a Literature Review - Komarov,Roman (2020)
Abstract Objective: To examine the results of various myocardial revascularization techniques in pediatric patients to better understand the strategies for surgical treatment of coronary artery pathologies. Methods: We analyzed 61 publications dedicated to the indications, methods, and results of coronary bypass surgery in children. Due to the small size of this cohort, case reports are also included in our review. Results: The main indications for coronary bypass grafting in children are Kawasaki disease, myocardial revascularization as a necessary procedure during the congenital cardiac surgery, to manage intraoperative iatrogenic damage to coronary arteries, and homozygous familial hypercholesterolemia. The use of internal thoracic arteries as conduits for coronary bypass grafting in children with Kawasaki disease showed significantly better results in long-term functionality compared to autovenous conduits (87% and 44%, respectively, P<0.001). Acute and late coronary events after arterial switch operation for the transposition of the great arteries, anomalous origin of the left coronary artery from the pulmonary artery, and left main coronary artery atresia are the main congenital heart diseases where surgical correction involves interventions on the coronary arteries. Conclusion: The internal thoracic artery is a reliable and durable conduit that demonstrates proven growth potential in children.